2019
DOI: 10.15376/biores.14.3.5488-5505
|View full text |Cite
|
Sign up to set email alerts
|

Management approach to motivation of white-collar employees in forest enterprises

Abstract: Employee motivation is a prerequisite for the effective development of the potential of human resources. Therefore, motivation processes are important. The aim of the paper was to define the motivational priorities of white-collar employees in forest enterprises. Following the research results, cluster analysis statistical methods were used to define employee groups with similar motivations. The research was carried out in 11 forest enterprises with 195 total respondents. The results indicated that it is possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Individual motivation to learn and improve is linked to the desire to use knowledge honestly, knowledge sharing and collaboration (Machuca and Costa 2012). Hitka et al (2019) found that communication in the workplace was one of the most highly valued motivation factors, and Paros (2021) found that timely communication influenced productivity. Imani et al (2020) and Huber (2017) state that relationships and communication play a critical role in organizational innovation.…”
Section: Communication and Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…Individual motivation to learn and improve is linked to the desire to use knowledge honestly, knowledge sharing and collaboration (Machuca and Costa 2012). Hitka et al (2019) found that communication in the workplace was one of the most highly valued motivation factors, and Paros (2021) found that timely communication influenced productivity. Imani et al (2020) and Huber (2017) state that relationships and communication play a critical role in organizational innovation.…”
Section: Communication and Relationshipsmentioning
confidence: 99%
“…Motives are elements of personality that are a driving force behind behaviors and express the psychological causes or reasons for that behavior (Hitka et al 2019). Motivation is a dynamic process that considers both personal and sociopsychological factors that interact with one another.…”
Section: Personal Characteristics and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the research outcomes indicate that, in contrast to blue-collar workers, managers and white-collar employees exhibit a preference for similar motivation factors, such as a conducive workplace atmosphere and effective teamwork. Hitka et al (2019) studied the motivational priorities of white-collar employees in forest enterprises. They determined that salary, workplace conditions and fair appraisal system are the key motivational factors.…”
Section: Introductionmentioning
confidence: 99%
“…Employment and labour productivity in the woodworking industry have also been studied by other authors (Merková and Drabek 2010;Burja and Mărginean 2013;Pang et al 2015;Chobanova and Georgieva 2017;Neykov et al 2018;Grzegorzewska et al 2020). Motivation and its factors are important aspects in determining the labour-force quality (Lorincová et al 2016;Hitka et al 2017Hitka et al , 2019. In addition, the labour productivity of the wood-based industry depends also on the level of plant technical equipment, the technologies applied, production innovativeness (Smardzewski 2009), and the quality of human resources (Hitka and Sirotiakovà 2011).…”
Section: Introductionmentioning
confidence: 99%